ANALYSIS OF TAX AVOIDANCE IN FINANCIAL STATEMENT FROM SHARIA ACCOUNTING PERSPECTIVE - Indahsari, Leny; Suryanto, Tulus; Noviarita, Heni; Fasa, Muhammad Iqbal (Universitas Gunadarma, 2024)
Tax evasion for companies in Indonesia is not a violation of the law where there are no civil sanctions. However, such activities are not justified in Islam. In Islam, an accounting system using Islamic sharia is a recording system that aims to get profits without any party feeling disadvantaged. The purpose of this study is to analyze tax scanning on financial statements from the perspective of Islamic accounting. The research method used in this study uses the Fixed Effect Model (FEM) with panel data from 2020-2022; the sample used is 10 company stocks included in the Jakarta Islamic Index. The results of FEM statistics showed that the company's profit variable, namely ROA, significantly negatively affected tax avoidance, and the company's sales growth variable significantly positively affected tax avoidance with a confidence level of 95 percent. Then the practice of tax avoidance in the perspective of Islamic accounting where the activity is not allowed because it will cause losses to other parties.